Role of current density in the degradation of LiNi0.6Co0.2Mn0.2O2 cathode material. (1st March 2019) - Wu, Borong; Bi, Jiaying; Liu, Qi; Mu, Daobin; Wang, Lei; Fu, Jiale; Wu, Feng
Abstract: The effect of different current density on the structure transformation of LiNi0.6 Co0.2 Mn0.2 O2 material is studied under a cut-off voltage (4.6 V). It shows that the capacity fading is accelerated at the high discharge current density. It is mainly caused by the structure instability of the material. When the current density increases, the loss of lithium on the surface of the material becomes severe, and the oxidation state becomes higher. The unit cell parameters also change, parameter a becomes larger, while the c becomes smaller. At the same time, the high discharge current density has a catalytic effect on the structural transformation, and in terms of high charging voltage, the surface structure changes to a rock salt phase. The cathode material is covered by a 3-nm-thick and discontinuous rock salt phase after cycling 50 times at the current density of 100 mA g −1 . However, when the material is cycled at the current density of 1000 mA g −1, the rock salt phase becomes thicker (5∼7-nm-thick) and more continuous, which leads to a fast capacity fading.